Social support as a mediator between social identity and college student’s stress - Ummu Umayyah (Department of Psychology, Universitas Negeri Yogyakarta, 2018)
This study aims to find social support as a mediator of social identity against student stress. This study uses a stage cluster random sampling technique, the subject of this study amounted to 375 students scattered on 7 faculties at Yogyakarta State University. The result of the research shows that the social identity level of students is high, social support is high and stress level is classified. The path analysis a proved significant with the value of 0.036 0.05, on path analysis proved significant with a value of 0.016 0.05, in path analysis proved significant with a value of 0.000 0.05, and path analysis was proved significant with value 0.000 0.05. Mediation analysis is evident and includes partial mediation.